Reduction of complications in femoral neck fracture fixation using femoral neck system: the importance of pre-compression technique and power bar position - Chen, Bin; Lin, Dongze; Lin, Fengfei; Liu, Wenge (Frontiers in Medicine, 2025)
BackgroundTo explore the causes of early- and mid-term complications and failures following femoral neck system (FNS) treatment for femoral neck fractures in young and middle-aged adults, to identify prevention and treatment strategies.MethodA retrospective analysis was conducted on the clinical data of 89 young and middle-aged adults patients with femoral neck fractures who received FNS treatment at our hospital between September 2019 and November 2021. Cases with early- and mid-term complications or failures were classified, and the potential causes and corresponding treatment measures were analyzed.ResultA total of 12 patients (13.5%) experienced complications, including femoral neck shortening in 9 cases (10.1%), lateral femoral cutaneous nerve injury in 1 case (1.1%), and internal fixation failure in 2 cases (2.2%). Univariable and multivariable analyses identified tip-apex distance (TAD) ≥ 25 mm, medial cortical comminution, poor reduction quality (Garden grades III–IV), and non-inferior power bar position as significant risk factors for complications. Patients treated with the pre-compression technique demonstrated a lower incidence of femoral neck shortening (0% vs. 17.6%) and significantly better hip function scores at 6-month and final follow-up compared to those without pre-compression.ConclusionStrict adherence to operational standards, proper surgical techniques, improved fracture reduction quality, and appropriate weight-bearing control can help reduce early- and mid-term complications following FNS fixation for femoral neck fractures in young and middle-aged adults. The use of the pre-compression technique for the power bar, along with its placement in the lower to middle part of the femoral neck, may reduce femoral neck shortening and the risk of internal fixation cut-out.